2020
DOI: 10.1016/j.celrep.2019.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ5 Internalizes Zika Virus during Neural Stem Cells Infection and Provides a Promising Target for Antiviral Therapy

Abstract: Highlights d CRISPR screens identify 92 GSC-specific factors linked to ZIKV infection d Integrin avb5 mediates ZIKV internalization into hNSCs providing two drug candidates d Integrin avb5 expression correlates with ZIKV susceptibility and neurotropism d Inhibition of avb5 alleviates ZIKV-induced pathology in hNSCs and in mouse brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 79 publications
(127 reference statements)
4
56
0
Order By: Relevance
“…As highly conserved molecules expressed by almost every cell type, integrins serve as entry receptors of several viruses, including Adenovirus [52], Foot-and-mouth disease virus [53], hantavirus [54], human coxsackievirus A9 [55], human echovirus 9 [56], and WNV [57]. A very recent study by Wang et al identified integrin avb5 as an entry receptor for ZIKV to establish an infection in neural stem cells [58]. Similarly, our data from ZIKV entry assay confirm that ITGAV is essential for the initiation of ZIKV internalization.…”
Section: Discussionmentioning
confidence: 99%
“…As highly conserved molecules expressed by almost every cell type, integrins serve as entry receptors of several viruses, including Adenovirus [52], Foot-and-mouth disease virus [53], hantavirus [54], human coxsackievirus A9 [55], human echovirus 9 [56], and WNV [57]. A very recent study by Wang et al identified integrin avb5 as an entry receptor for ZIKV to establish an infection in neural stem cells [58]. Similarly, our data from ZIKV entry assay confirm that ITGAV is essential for the initiation of ZIKV internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between host attachment factor expression and viral tropism in vivo have not been established. Some flavivirus attachment factors (for example, TAM and integrin receptors) capable of binding virions also transduce signals into target cells, which has the potential to augment infection and further complicates the role and definition of host attachment molecules [39][40][41][42] .…”
Section: E-diismentioning
confidence: 99%
“…ZIKV preferentially infects neuronal progenitor cells (NPCs) in the developing foetal brain and has also been found in tissues outside the central nervous system (CNS), including the eyes, testis, and female reproductive tract organs [16][17][18][19]. However, few reports focus on the basis of ZIKV cellular and tissue tropism [20][21][22]. ZIKV infection induces a series of host cell innate immune responses, pro-inflammatory responses, and humoral immune responses by producing protective and neutralizing antibodies in humans [17,23,24].…”
Section: Introductionmentioning
confidence: 99%